Adipose-Derived Stromal Cells for Treatment of Patients with Chronic Ischemic Heart Disease (MyStromalCell Trial): A Randomized Placebo-Controlled Study - Abbas Ali Qayyum; Anders Bruun Mathiasen; Naja Dam Mygind; Jørgen Tobias Kühl; Erik Jørgensen; Steffen Helqvist; Jens Jørgen Elberg; Klaus Fuglsang Kofoed; Niels Groove Vejlstrup; Anne Fischer-Nielsen; Mandana Haack-Sørensen; Annette Ekblond; et al. (Stem Cells International)
We aimed to evaluate the effect of intramyocardial injections of autologous VEGF-A165-stimulated adipose-derived stromal cells (ASCs) in patients with refractory angina. MyStromalCell trial is a randomized double-blind placebo-controlled study including sixty patients with CCS/NYHA class II-III, left ventricular ejection fraction > 40%, and at least one significant coronary artery stenosis. Patients were treated with ASC or placebo in a 2 : 1 ratio. ASCs from the abdomen were culture expanded and stimulated with VEGF-A165. At 6 months follow-up, bicycle exercise tolerance increased significantly in time duration 22 s (95%CI −164 to 208 s) (P=0.034), in watt 4 (95%CI −33 to 41, 0.048), and in METs 0.2 (95%CI −1.4 to 1.8) (P=0.048) in the ASC group while there was a nonsignificant increase in the placebo group in time duration 9 s (95%CI −203 to 221 s) (P=0.053), in watt 7 (95%CI −40 to 54) (P=0.41), and in METs 0.1 (95%CI −1.7 to 1.9) (P=0.757). The difference between the groups was not significant (P=0.680, P=0.608, and P=0.720 for time duration, watt, and METs, resp.). Intramyocardial delivered VEGF-A165-stimulated ASC treatment was safe but did not improve exercise capacity compared to placebo. However, exercise capacity increased in the ASC but not in the placebo group. This trial is registered with ClinicalTrials.gov NCT01449032.